A Convenção de Ramsar e a proteção jurídica das áreas úmidas brasileiras - Darold, Fernanda Ribeiro (2022)
The present dissertation aims to discuss the legal protection of Brazilian wetlands (hereby AUs), in view of the provisions of the Ramsar Convention, having as a hypothesis the absence of specific legal protection for AUs by Brazilian environmental law. To this end, it addresses the socio-environmental importance of AUs, presents the Ramsar Convention as an instrument of legal protection of AUs and, finally, its applicability in the Brazilian constitutional order. Regarding the methodology for carrying out this research, as for the objective, it is a descriptiveanalytical research. Regarding the data source, this is a predominantly bibliographic and documentary research, considering that doctrines, legislation and statistical data dedicated to understanding the protection and conservation of AUs were researched. It was seen that, although a substantial portion of the Brazilian territory is covered by AUs, inventories of these areas still remain incomplete, making it difficult to elaborate specific public politics to these zones. Therefore, the Brazilian legal system lacks a coherent national policy for the sustainable management and protection of AUs, mainly due to the absence of standardized criteria by which AUs are defined and outlined and of a national classification of AUs, which takes into account consideration of specific ecological conditions. There is, therefore, a need to pass laws that grant greater protection to AUs, as the destruction of these areas directly impacts the social, economic, cultural and ecological conditions of the world's population.